PENERAPAN ASAS FUNGSI SOSIAL HAK ATAS TANAH DALAM PUTUSAN NOMOR 28/G/PU/2019/PTUN.PBR - Amasta, Andrea Winda; Paulus, Rekky Sean (The Juris, 2024)
This paper will discuss the Application of Land Social Function in Law Number 2/2012 on Land Acquisition for Public Interest. To find a solution to this problem, document and literature searches are required in this research. The results show that the regulation of land acquisition norms in Article 5 of Law Number 2/2012 on Land Acquisition for Public Interest has applied the principle of social function of land, because land acquisition carried out by the government as stipulated in Article 5 is an act for the construction of public facilities that can be used by the entire community. The application of Article 5 of Law Number 2/2012 often triggers problems, especially if the land taken over for development is productive land used by the community as a source of their livelihood and will result in the loss of people’s livelihoods. As a result, it is very natural that some people refuse and do not want to release their land even though they have been promised a compensation value. Therefore, more knowledge and understanding of the social function of land is needed as an effort to realise justice and welfare, especially for those who are given their land without ignoring aspects of legal certainty as a characteristic of the rule of law.